2009
DOI: 10.1111/j.1365-2966.2009.15320.x
|View full text |Cite
|
Sign up to set email alerts
|

Too large and overlooked? Extended free-free emission towards massive star formation regions

Abstract: We present Australia Telescope Compact Array observations towards six massive star formation regions, which, from their strong 24 GHz continuum emission but no compact 8 GHz continuum emission, appeared good candidates for hypercompact H ii regions. However, the properties of the ionized gas derived from the 19 to 93 GHz continuum emission and H70α+ H57α radio recombination line data show the majority of these sources are, in fact, regions of spatially extended, optically thin free–free emission. These extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Several UC H ii regions have been observed to be embedded in extended radio continuum emission (Kurtz et al 1999). The recent work of Longmore et al (2009) also found a significant fraction of 6.7 GHz methanol maser sources that had no 3.6 cm radio continuum as measured by Walsh et al (1998), to have extended emission with the total flux at times being several orders of magnitude discrepant from previous limits. Missing an extended radio continuum component due to spatial filtering of an interferometer can lead to errors in the classification and inferred age of the source.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Several UC H ii regions have been observed to be embedded in extended radio continuum emission (Kurtz et al 1999). The recent work of Longmore et al (2009) also found a significant fraction of 6.7 GHz methanol maser sources that had no 3.6 cm radio continuum as measured by Walsh et al (1998), to have extended emission with the total flux at times being several orders of magnitude discrepant from previous limits. Missing an extended radio continuum component due to spatial filtering of an interferometer can lead to errors in the classification and inferred age of the source.…”
Section: Resultsmentioning
confidence: 65%
“…With the exception of 39.39-0.14, no extended emission was found in the sources. Although this does not rule out the presence of extended emission on scales larger than 30 , it suggests a lack of continuum sources similar to those discovered by Longmore et al (2009). In the case of 39.39-0.14, the extended emission led to the discovery of a counterpart at 3.6 cm leading to reclassification of the nature of radio continuum emission from optically thick to optically thin emission between 3.6 cm and 1.3 cm.…”
Section: Resultsmentioning
confidence: 97%
“…Longmore et al (2009) report the detection of spatially extended, optically thin freefree emission in the fields of six 6.7 GHz CH 3 OH masers previously reported as 3.6 cm continuum nondetections (Walsh et al 1998), and caution that the evolutionary state of CH 3 OH maser sources may be misconstrued if extended free-free emission is missed in highresolution interferometric observations. We believe that our cm continuum study of EGOs is robust against such misclassification for several reasons.…”
Section: (See Also C11)mentioning
confidence: 99%
“…(3) In several cases, the extended HII regions reported by Longmore et al (2009) are offset from the CH 3 OH maser positions, and the masers are more closely associated with HC HII regions or with 3 mm emission attributed to dust. So, as Longmore et al (2009) note, the presence of more evolved HII regions in the vicinity of 6.7 GHz CH 3 OH masers may simply be due to the clustered nature of massive star formation. In fact, we see several potential examples of this in our data.…”
Section: (See Also C11)mentioning
confidence: 99%
“…In one of these rotating cores, G24 A1, the presence of an early-type star is witnessed by an embedded hypercompact (HC) Hii region, first detected at 1.3 cm by Codella et al (1997) and later studied at very high-angular resolution at 1.3 and 0.7 cm by Beltrán et al (2007). The properties of the ionized gas have also been studied through continuum emission and recombination lines by Galván-Madrid et al (2008) and Longmore et al (2009). This HC Hii region, which has a diameter of < ∼ 0.…”
Section: Introductionmentioning
confidence: 99%